Care-experienced cHildren and young people's Interventions to improve Mental health and wEll-being outcomes: Systematic review (CHIMES) protocol. Issue 1 (26th January 2021) - Evans, Rhiannon; Boffey, Maria; MacDonald, Sarah; Noyes, Jane; Melendez-Torres, G.J.; Morgan, Helen E; Trubey, Rob; Robling, Michael; Willis, Simone; Wooders, Charlotte
Abstract : Introduction: The mental health and well-being of children and young people who have been in care (ie, care-experienced) are a priority. There are a range of interventions aimed at addressing these outcomes, but the international evidence-base remains ambiguous. There is a paucity of methodologically robust systematic reviews of intervention effectiveness, with few considering the contextual conditions under which evaluations were conducted. This is important in understanding the potential transferability of the evidence-base across contexts. The present systematic review will adopt a complex systems perspective to synthesise evidence reporting evaluations of mental health and well-being interventions for care-experienced children and young people. It will address impact, equity, cost-effectiveness, context, implementation and acceptability. Stakeholder consultation will prioritise a programme theory, and associated intervention, that may progress to further development and evaluation in the UK. Methods and analysis: We will search 16 bibliographic databases from 1990 to June 2020. Supplementary searching will include citation tracking, author recommendation, and identification of evidence clusters relevant to included evaluations. The eligible population is children and young people (aged ≤25 years) with experience of being in care. Outcomes are (1) mental, behavioural or neurodevelopmental disorders; (2) subjective well-being; (3) self-harm; suicidal ideation; suicide. Study quality will be appraised with methodologically appropriate tools. We will construct a taxonomy of programme theories and intervention types. Thematic synthesis will be used for qualitative data reporting context, implementation and acceptability. If appropriate, meta-analysis will be conducted with outcome and economic data. Convergent synthesis will be used to integrate syntheses of qualitative and quantitative data. Ethics and dissemination: We have a comprehensive strategy for engagement with care-experienced children and young people, carers and social care professionals. Dissemination will include academic and non-academic publications and conference presentations. Ethical approval from Cardiff University's School of Social Sciences REC will be obtained if necessary. PROSPERO registration number: CRD42020177478.